Design of nanostructured hybrid materials: twin polymerization of urethane-based twin prepolymers. Issue 55 (12th September 2018) - Uhlig, D.; Spange, S.; Seifert, A.; Nagel, K.; Anders, S.; Kroll, L.; Stoll, R.; Thielbeer, F.; Müller, P.; Schreiter, K.
Abstract : Organic–inorganic hybrid materials with urethane functionalities were obtained by simultaneous twin polymerization of twin prepolymers in combination with the twin monomer 2, 2′-spirobi[4 H -1, 3, 2-benzodioxasiline]. Abstract : Organic–inorganic hybrid materials with urethane functionalities were obtained by simultaneous twin polymerization of twin prepolymers in combination with the ideal twin monomer 2, 2′-spirobi[4 H -1, 3, 2-benzodioxasiline]. The twin prepolymers consist of a urethane-based prepolymer with reactive terminal groups which can react during the twin polymerization process. Nanostructured hybrid materials with integrated dialkylsiloxane crosslinked urethane structures, phenolic resin and SiO2 are obtained in a one pot process. The effects of the polymerization temperature as well as those of various catalysts and reagent ratios on the polymerization behavior were investigated. The molecular structures of the obtained materials were determined by 13 C- and 29 Si-{ 1 H}-CP-MAS NMR spectroscopies. HAADF-STEM-measurements were performed to prove the distribution of silicon in the hybrid material.